Хелени или Ромеи – Судир на наследствата - Jovanovski, Dalibor, Vasilevska, Ivanka (Институт за национална историја, 2019)
After the establishment of the new Greek state in 1830, the Greeks looked into the past as a model for creating of their identity which did not exist before. However, there were two different ideal types for tracing of their origins. The supporters of the ancient Hellenic ideology sought to shape the identity of the new Greek state within the framework of the ancient Hellenic ideal by denying and excluding the Byzantine and Ottoman past form the newly projected modern Greek identity. Thus, the clash between the Hellenic way of interpreting the Greek past and the Romeic was inevitable. The tensions between the Hellenic and Romeic models was reflected in the distinction between katharevousa and demotic Greek language. Here we are examining the tensions between the two mutually opposed forces in the cultural and linguistic field. The rift between these two concepts exists even today despite the fact that the wast majority of the Greeks affiliated themselves with the Ancient Greek tradition.
Keywords: Грција, Македонија, антика, културно наследство.